PERENCANAAN SABO DAM SEBAGAI BANGUNAN PENGENDALI SEDIMEN PADA SUNGAI TALANG KOTA PADANG PANJANG - Oskar Roy; Surya Eka Priana; Elfania Bastian (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Sedimentation is the process of forming sedimentary material deposits or fragments of rocks, minerals and organic materials that drift and move in the direction of the flow of river water. There are various ways of holding it, such as being pushed, carried by jumping up and down and some are dissolved. Sedimentation in the Talang River which occurred at 185,764 m³/year resulted in silting, thereby reducing the water holding capacity of the Talang River. The construction of the Sabo Dam is one solution that can be done to control sedimentation in the river. The purpose of this study is to design a sediment control weir that is safe for stability with the largest sediment storage volume. The method used in this research is to compare the hydraulic design of the Sabo building at two specified locations (STA 0+200 and STA 201+400), then stability analysis is carried out based on the forces that occur and the volume of sediment that can be accommodated. Based on the results of stability analysis at two locations, it was found that the STA 201+400 weir was safe against shearing, overturning, bearing capacity and piping. The sediment volume that can be retained is 156,206.85 m³ and Sabo will be full of sediment after 8 months. Meanwhile, at the location of STA 0+200 the sediment that can be retained is 7,913,787 m and will be full after 4 months. The construction of the Sabo Dam at STA 201+400 is expected to reduce sedimentation that occurs in the Talang River.